2015
DOI: 10.3384/lic.diva-114396
|View full text |Cite
|
Sign up to set email alerts
|

Growth in established SMEs : Exploring the innovative and ambitious firm

Abstract: The growth of firms is a complex but relevant subject for different stakeholders, such as owners, who want returns on their investment, and society, where firms are vessels for jobs and job creation. Despite the vast amount of research conducted on firm growth and factors associated with firm growth, there is no coherent body of knowledge, and the average firm is not growing.This research focuses on growth in established small and medium-sized enterprises (SMEs), i.e. firms that have passed the startup phase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…Regarding the determinants of MSMEs growth, several previous studies have observed that factors such as company resources, human capital (age, experience and attitude), government and environmental characteristics are essential for the intention of managers/ owners to grow (Ali, 2018;Gancarczyk and Zabala-Iturriagagoitia, 2015;Neneh and Vanzyl, 2014;Wasilczuk and Zięba, 2009). In line with this opinion, the findings of Uddenberg (2015) assess that neither lack of growth cannot be explained by the manager/owner's perception of the company's possibility of growth but rather how the support system works. Moreover, there is no evidence that differences in growth rates are associated with different levels of growth opportunities.…”
Section: Intention To Growth Modelmentioning
confidence: 61%
See 3 more Smart Citations
“…Regarding the determinants of MSMEs growth, several previous studies have observed that factors such as company resources, human capital (age, experience and attitude), government and environmental characteristics are essential for the intention of managers/ owners to grow (Ali, 2018;Gancarczyk and Zabala-Iturriagagoitia, 2015;Neneh and Vanzyl, 2014;Wasilczuk and Zięba, 2009). In line with this opinion, the findings of Uddenberg (2015) assess that neither lack of growth cannot be explained by the manager/owner's perception of the company's possibility of growth but rather how the support system works. Moreover, there is no evidence that differences in growth rates are associated with different levels of growth opportunities.…”
Section: Intention To Growth Modelmentioning
confidence: 61%
“…The micro, small and medium enterprises (MSMEs) sector is a pillar of a nation's economic progress. However, the issue of MSME growth is still a significant topic today (Uddenberg, 2015;Wasilczuk and Zięba, 2009). In economic theory, growth is seen as a phenomenon that occurs to achieve maximum profit, but the reality is that not all MSMEs owners want to develop their businesses to maximise profits (Neneh and Vanzyl, 2014;Verheul and Mil, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, most scholars considerthe the important impacting factors in enterprise resources, human resources management, enterprise innovation and system suitability. While the financial situation [4] (Earnings per share, net profit margin growth, asset-liability ratio) are also an essential indicator as well (Uddenberg, 2015). Tran (2015) his research was conducted by using a multiple single-case studies methodology to gain a deeper understanding of the adoption factors behind New South Wales (NSW) micro enterprises [5].…”
Section: Literature Reviewmentioning
confidence: 99%